Critical analysis of extension and research gap in adoption of groundnut (Arachis hypogaea L.) production technology in Dharwad district, Karnataka: CRITICAL ANALYSIS OF EXTENSION AND RESEARCH GAP IN ADOPTION OF GROUNDNUT - A BHEEMAPPA; R K PATIL (Journal of Oilseeds Research, 2013)
A research study on critical analysis of extension and research gap in groundnut (Arachis hypogaea L.) production technology among the farmers of Dharwad district was conducted during 2010-2011. The Ex-post-facto research design was employed to collect the data from 150 sample farmers cultivating groundnut crop. The focus group discussions were also conducted for the triangulation of the collected data. The results revealed the existence of technological gap in zinc application (84.5%), Rhizobium seed treatment (79.3%), control of diseases (67.4%) and gypsum application (51.9%). The major extension strategies expressed were the ensured availability of critical inputs nearby villages at the required time of field operations (100%), popularizing seed production (84.5%), implementing effective extension programmes(81.5%), and information dissemination through electronic media and extension literature (63.7%). All the farmers expressed the research priorities such as screening of suitable spreading, high yielding, collar rot resistant, drought tolerant and table purpose varieties. The suitable seed drill to take up groundnut sowing in paddy fallow land through moisture conserving, popularising green pod harvester and technology for controlling collar rot disease were the other research priorities expressed for increasing area and productivity of groundnut crop.